Evaluation of Spalangia endius and Muscidifurax sp. (Hymenoptera, Pteromalidae) as controller of Musca domestica en el Peru - Inciso, Edgar (2006)
In this work we compared the parasitoid activity of the microhymenopterans Spalangia endius and Muscidifurax sp. on the pupae of Musca domestica. The better temperature for the reared was of 25 °C. The cycle of S. endius was completed in 22,6 days, while in Muscidifurax sp. in 14,8 days. The cycle duration was inversely related to temperature, in the females was highest than males. The longevity was similar in both microhymenopterans species (20,7 days in S. endius and 18,6 days in Muscifurax sp.). Spalangia endius oviposited on 175 pupae of M. domestica in 15 days; this value was highest than Muscidifurax that oviposited 140 pupae in 16 days. In both species the highest posture occurred in the third day. Musca domestica pupae with two maturation days were the more parasited; S. endius with 66,4% and Muscidifurax sp. with 60,2% of effective parasitism. The better number of M. domestica pupae was 10 (10:1). We conclude that under laboratory conditions, S. endius can be an efficient biological controller of pustules of M. domestica.